Informação e memória no espaço público da cidade: análise de logradouros com estatuária em João Pessoa - Silva, Tahis Virgínia Gomes da (2021)
Public spaces in cities enable socio-cultural relations, making it possible to affirm that the city is a place for the production and consumption of information and the construction of social memory. This thesis aims to analyze the relationship between information and memory triggered by the places with statuary in the João Pessoa city / PB, based on the hypothesis that such elements, while potentially informational, communicational, memorialistic and patrimonial artifacts can trigger the relationship between information and memory. The theoretical framework that underlies the reflections of this research is the notion of space, as a practiced place. The data collection technique adopted is qualitative observation, aided by the use of images, from the on-site visitation of the selected spaces together with the virtual visitation through navigation in the Google Maps Street view. It was concluded that this study made it possible to perceive the construction of meanings of belonging constituted by the meaning of the urban public space of the city, as a field for the construction of information and memorialistic and patrimonial communication, contributing to the research of the PPGCI / UFPB offering subsidies to expand the reflection on the relationship between Information and Memory in the scope of Information Science.